32 Cognitive behavioural therapy vs standardised medical care for adults with dissociative non-epileptic seizures (codes): update on a pragmatic randomised controlled trial. Issue 8 (13th July 2017) - Goldstein, LH; Chalder, T; Carson, AJ; Landau, S; McCrone, P; Medford, N; Murray, J; Reuber, M; Richardson, MP; Stone, J; Perdue, I; Johnston, S; et al.
Abstract : Objective: Our UK-based multi-centre randomised controlled trial (RCT) will evaluate the clinical and cost effectiveness of Cognitive Behavioural Therapy (CBT) (plus Standardised Medical Care – SMC) in contrast to SMC alone in adults with dissociative (psychogenic nonepileptic) seizures (DS). This trial is powered to provide evidence for the effectiveness of CBT tailored to DS in this patient group. Method: Following receipt of their diagnosis and further information about their disorder from a neurologist/epilepsy specialist, recruited adults with DS have their DS frequency monitored every two weeks. They then attend a psychiatric assessment three months later and receive further DS-related information. If patients' DS have continued to occur within the previous 8 weeks and they meet other study eligibility criteria, they are asked to consent to complete baseline measures and are then randomised to receive either 12 sessions of CBT (and a booster session) plus SMC or SMC alone. DS frequency continues to be monitored fortnightly. Follow-up data are collected at 6 and 12 months after randomisation. Our primary outcome is monthly DS frequency at 12 months' post randomisation; we will also evaluate outcomes relating to DS severity/freedom, psychological status, quality of life, and formal/informal service use. We also plan to undertake qualitative interviews of participants' and healthcare professionals' experiences of the interventions. Results: Over 40 clinical services in England, Scotland and Wales have been recruiting and/or treating patients for the trial. By late October 2016 at least 592 patients had been recruited from neurology/epilepsy services to the screening phase; we had randomised at least 266 patients into the RCT. We have been undertaking both 6 and 12 month follow-up assessments. Conclusion: We will present more details about the design and up-to-date progress of the trial. Despite many challenges posed by an RCT of this extent and with this patient group, our trial illustrates both the need for care pathways for this patient group and that large numbers of patients with DS are interested in research into and treatments for their disorder. Funding: NIHR HTA reference 12/26/01; ISRCTN05681227 .